Acţiuni de răspuns la consecinţele şi riscurile asociate schimbărilor climatice asupra calităţii vieţii - Humă, Cristina (Calitatea Vieții, 2019)
The study presents a series of actions by which society is currently addressing the issue of climate change (global). We are considering the measures for mitigation and adaptation to the consequences of climate change taking place at the international, European and national level, with emphasis on the response policies of our country. We refer to the solutions that are being taken in Romania to reduce climate change in programmes aimed at the population, public institutions, administrative-territorial units and aiming to encourage the use of renewable energy and less polluting road transport. Concerning the national policy for adaptation to the consequences of climate change, the paper highlights some measures aimed at preventing situations with destructive potential for people and material goods, ensuring the protection of the persons employed, ensuring the social protection of the low income population categories, the development of the natural risk insurance system, the development of the irrigation system for agricultural crops. The analysis was carried out using statistical data (Eurostat, European Commission, Pew Research Center, National Institute of Statistics, etc.), strategic documents, normative acts, specialized papers, information contained in the websites of some institutions.